ERRECTING TELCOMMUNICATION MAST IN RESIDENTIAL AREA: HEALTH CHALLENGES; A CASE STUDY OF DAMBA, GUSAU LOCAL GOVERNMENT AREA ZAMFARA STATE, NIGERIA - MUHAMMAD , S.B.; SANI, I. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The cases of cancer especially in women and children in Zamfara are drastically increasing and seem to be out of control. Therefore, this research seeks to investigate radiation from telecommunication mast with site number: ZM0017 at Garaza in Damba. Theoretical calculation of power density and a well-structured questionnaire was deployed to investigate the effect of radiation from the telecommunication mast within a 500m radius of its location. The hazard profile showed that 70.6% of the respondent have different and/or multiple symptoms, however, there were no cancer-like symptoms, while 29.4% were symptoms free. The calculated power density from the distance of 5m to 120m away from the mast in the step of 5m was found to be within the range of 0.0000009549 to 0.000000002387, and from a distance of 120m up to 160m away from the mast in steps of 20m were found to be within the range of 0.000000001658 to 0.0000000003532 and from 300m up to 500m in the step distances of 40m were found to be within the range of 0.0000000002653 to 0.0000000009549 , and finally at a distance of 550m was found to be 0.00000000007892. All of these calculated power densities at variable distances from the mast were very much below the ICNIRP standard adopted by African and Asian countries. The duration of the dwellers in the area, being a newly developed area, was not up to ten years. Thus, the effect of radiation might not be fully accessed due to short-time exposure. There were numerous cases of illness related to radiation but no single case of cancer was found in the area.